FIGURE 3. Paralomis makarovi n in Four new species of the family Lithodidae (Decapoda: Anomura) from the collections of the National Museum of Natural History, Smithsonian Institution - Hall, Sally; Thatje, Sven (Zenodo, 2009)
FIGURE 3. Paralomis makarovi n. sp. a–d, f–g: male holotype, 23.8 mm CL (USNM 1122582), Bering Sea, Bowers Bank, 54°30'N, 179°17'E, 629 m. e: female paratype 24 mm CL (USNM 1122582). (a) whole organism, dorsal. (b) right chela, lateral. (c) ocular peduncles, dorsal. (d) male abdomen. (e) female abdomen. (f) rostral spines, dorsal. (g) antennal acicle, dorsal. Scale bar = 5 mm for a, b; 1 mm for c–g. Published as part of Hall, Sally & Thatje, Sven, 2009, Four new species of the family Lithodidae (Decapoda: Anomura) from the collections of the National Museum of Natural History, Smithsonian Institution, pp. 31-47 in Zootaxa 2302 on page 37, DOI: 10.5281/zenodo.191756